Application and discussion of various crack closure models to predict fatigue crack growth in 6061-T651 aluminium alloy - Ribeiro, Victor [UNESP] (2021)
Fatigue is one of the main causes of failures as well as mechanical fractures in structural details made of aluminium alloys under cyclic loading, where the materials (during the crack growth process) are subject to the stress R-ratio effects and crack closure phenomenon. In this research work, a comparison of the effect of various crack closure/opening models on the fatigue crack growth behaviour of 6061-T651 aluminium alloy is presented. The crack closure models under consideration are the following: Elber; Katcher and Kaplan; Clerivet and Bathias; Schijve; Zhang; Newman; Savaidis; Codrington-Kotousov; and, Correia. A comparison between these models and experimental data is also done. Deterministic quadratic relations based on experimental results between U vs R and Reff vs. R are suggested and compared with various crack closure models under consideration, where U is a quantitative parameter function of crack opening and closing concept. This investigation into the crack closure/opening effects is made using experimental results from the first cycle and stabilised measurements (U1 and Us). Correia's and Newman's models presented a better agreement with the experimental results (Ud,s or Reff,s). In this study, the crack closure quantitative parameters based on the first cycle and stabilised measurements reveal to be different, where Uand Reff vary with the crack growth process, which suggests the assumptions listed by Hudak and Davidson, Ellyin, and Correia seem to be correct. Therefore, it can be concluded that the simultaneous monitoring of CTOD-based experimental measurements of the crack closure effects and getting the crack tip stress–strain field based on digital image correlation (DIC) measurements, supported by analytical/numerical solutions, seems to be a good way to describe the fatigue crack growth.